Induction of an auto-anti-IgE response in rats. III. Inhibition of a specific IgE response. - Marshall, J S (1989)
An auto-anti-IgE response was induced in conventional (PVG-RT1U and high IgE-producing (BN) rat strains by immunization with a highly purified rat IgE myeloma IR2. Earlier work established that total serum IgE levels were decreased by this procedure (Marshall & Bell, 1985) but only in the PVG-RT1U strain. IR2-immunized rats were tested for their ability to produce a specific IgE response to ovalbumin (OVA). The primary anti-OVA IgE response was inhibited by 60-75% in both rat strains, regardless of whether the total serum levels of IgE were reduced. The secondary IgE response to OVA was also inhibited in anti-IgE-producing animals but not in rats primed with OVA before anti-IgE induction. The inhibition of the anti-OVA response was isotype specific; the IgG response to OVA was unaffected. These studies may help elucidate the regulatory role played by naturally occurring anti-IgE antibodies found particularly in atopic individuals.